The Application of Problem Based Learning Model To Increase Students Achievement In Indonesian Subject - Putri, Mareta Nugraha (Universitas Sebelas Maret, 2020)
The aim of this study was to increase the third grade elementary students learning achievement on Indonesian subject by applying Problem Based Learning (PBL) model. The research done was a Classroom Action Research (CAR) that had been done in two cycles which each cycle consisted of one meeting. The steps of each cycle were planning, applying, observing and reflecting. Each meeting had evaluation test to determine students learning achievement. On the fist cycle, there were 60.86% student had completed their study. In the second cycle, there were 95,65% students had completed their study. This results showed that Problem Based Learning (PBL) model can increase students learning achievement especially in Indonesian subjects of the third grade SD Negeri 1 Keden Pedan.